The Uniaxial Compressive Strength of Soft Rock - D. S. Agustawijaya (Civil Engineering Dimension, 2007)
Soft rock is a term that usually refers to a rock material with a uniaxial compressive strength (UCS) less than 20 MPa. This low strength range might be influenced by physical characteristics, such as size, saturation, weathering and mineral content. A number of uniaxial compression tests have been conducted onto soft rock samples. The results showed that the strength reduced significantly in saturation. The reduction was also caused by weathering, the strength of distinctly weathered rocks were lower than that of partially weathered rocks. In conjunction with the uniaxial compression test, point load strength index tests, IS(50), have also been conducted in order to obtain a correlation between the UCS and the point load strength index IS(50). The results showed that the IS(50) could well be correlated with the UCS. A conversion factor of 14 is proposed for soft rock materials.